Weaving Language and Learning in Negotiating for Meaning - Garcia, Regina Via (JPAIR Multidisciplinary Research, 2020)
Achieving an understanding of interlocutors in an English classroom is essential in successful communication, learning, and second language acquisition. Through these interactions, interlocutors can negotiate meaning by changing the linguistic form, conversational structure, and message content, or all three. This qualitative content analysis research focuses on the interactions produced between teacher and student or between the students themselves with the use of Michael Long’s Negotiation for Meaning (NfM). The research, conducted in Compostela Valley State College Main Campus, involved five (5) sections of first-year college students enrolled in General Education 2 - Purposive Communication along with their respective instructors. Interactions throughout the class were recorded and then transcribed for further analysis. According to the findings, three (3) signals from NfM are primarily utilized to achieve meaning; comprehension check, clarification request, and confirmation check. These signals functioned in the interaction through eliciting understanding, correcting, probing, recalling, and clarifying. The most used signal was a clarification request, and the most used function of these signals is understanding. The findings suggest that the negotiation in the interaction mostly required previous utterances to be clarified and that the main goal of negotiation is to achieve comprehension of the meaning being negotiated.